Liver-bone crosstalk in non-alcoholic fatty liver disease: Clinical implications and underlying pathophysiology - Zhao, Jiahui; Lei, Hongyan; Wang, Tianyi; Xiong, Xuelian (Frontiers in Endocrinology, 2023)
Osteoporosis is a common complication of many types of chronic liver diseases (CLDs), such as cholestatic liver disease, viral hepatitis, and alcoholic liver disease. Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent metabolic liver disease, affecting almost one third of adults around the world, and is emerging as the dominant cause of CLDs. Liver serves as a hub for nutrient and energy metabolism in the body, and its crosstalk with other tissues, such as adipose tissue, heart, and brain, has been well recognized. However, much less is known about the crosstalk that occurs between the liver and bone. Moreover, the mechanisms by which CLDs increase the risk for osteoporosis remain unclear. This review summarizes the latest research on the liver–bone axis and discusses the relationship between NAFLD and osteoporosis. We cover key signaling molecules secreted by liver, such as insulin-like growth factor-1 (IGF-1), fibroblast growth factor 21 (FGF21), insulin-like growth factor binding protein 1 (IGFBP1), fetuin-A, tumor necrosis factor-alpha (TNF-α), and osteopontin (OPN), and their relevance to the homeostasis of bone metabolism. Finally, we consider the disordered liver metabolism that occurs in patients with NAFLD and how this disrupts signaling to the bone, thereby perturbing the balance between osteoclasts and osteoblasts and leading to osteoporosis or hepatic osteodystrophy (HOD).